2020
DOI: 10.1016/j.heliyon.2020.e03416
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential maturity indicators for harvesting cacao

Abstract: Cocoa production is a complex process where the conditions of the raw materials decisively impact the final quality of the product. Three universal clones (CCN51, ICS95, and TSH565) from the Department of Huila in Colombia were evaluated to characterize the ripening process of cocoa fruits. Maturity indicators were identified by following the evolution of basic fruit characteristics, including size, weight, seed count, depth and distance between grooves, width and length of the apex, diameter and length of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
1
14
0
8
Order By: Relevance
“…While Gu et al (2013) reported that the flavonoid content for cocoa beans of different origin ranged from 3.50 to 12.62 mg epicatechin equivalents/g. The differences in the contents can be explained by several factors such as cocoa cultivars, geographical location, different maturity stages, postharvest operations, fermentation and drying, extraction procedures and analytical methodologies used in the assessment (Urbańska and Kowalska, 2019; Rojas, García, Cerón, Ortiz, & Tarazona, 2020;Santander Muñoz, Rodríguez Cortina, Vaillant, & Escobar Parra, 2020;Plaza et al, 2017).…”
Section: Polyphenols Contents and Antioxidant Capacity Of Cocoa Beansmentioning
confidence: 99%
“…While Gu et al (2013) reported that the flavonoid content for cocoa beans of different origin ranged from 3.50 to 12.62 mg epicatechin equivalents/g. The differences in the contents can be explained by several factors such as cocoa cultivars, geographical location, different maturity stages, postharvest operations, fermentation and drying, extraction procedures and analytical methodologies used in the assessment (Urbańska and Kowalska, 2019; Rojas, García, Cerón, Ortiz, & Tarazona, 2020;Santander Muñoz, Rodríguez Cortina, Vaillant, & Escobar Parra, 2020;Plaza et al, 2017).…”
Section: Polyphenols Contents and Antioxidant Capacity Of Cocoa Beansmentioning
confidence: 99%
“…The important factors during the fruit ripening process are the changes in moisture content, weight, and size of the beans. Rojas et al (2020) suggested that the weight of fruit, number of seeds, and fruit color and firmness could be used as harvest indicators while fruit size was not recommended as an indicator of ripeness. During physiological ripening, translocation of nutrients in the beans will stop.…”
Section: Cocoa Quality Evaluation Weight Of Harvested Fruitmentioning
confidence: 99%
“…Menurut Anna (2011) tingkat kemasakan buah untuk menghasilkan biji bermutu tinggi minimal adalah 60%, namun menurut Prawoto (2014) tanda-tanda kematangan buah kakao dipengaruhi oleh klon dan faktor lingkungan. Oleh karena itu, pengetahuan terhadap ciri morfologi kematangan buah secara spesifik lokasi merupakan referensi penting bagi pemanen untuk memperoleh buah dengan kemasakan tepat (Rojas et al, 2020).…”
Section: Abstrakunclassified
“…Pemanen cenderung menggunakan warna merah-semburat kuning atau merah-jingga sebagai indikator waktu panen bagi kedua klon, yang sebenarnya hanya tepat untuk DR 2 (Tabel 3). Rojas et al (2020) Tetapi dugaan ini membutuhkan pembuktian lebih lanjut. Ketepatan panen juga dipengaruhi umur pemanen (Tabel 8).…”
Section: Analisis Panenunclassified